2004
DOI: 10.1038/sj.ijo.0802611
|View full text |Cite
|
Sign up to set email alerts
|

School-based obesity prevention in Chilean primary school children: methodology and evaluation of a controlled study

Abstract: OBJECTIVE:To assess the impact of a 6 months nutrition education and physical activity intervention on primary school children through changes in adiposity and physical fitness. DESIGN: Longitudinal school-based controlled evaluation study. SUBJECTS: Children from 1st to 8th grade, 2141 in intervention and 945 in control schools. INTERVENTION: Nutrition education for children and parents, 'healthier' kiosks, 90 min of additional physical activity (PA) weekly, behavioral PA program and active recess. MEASUREMEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
230
1
10

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(249 citation statements)
references
References 33 publications
8
230
1
10
Order By: Relevance
“…Where studies 38,39,51,55,56 reported mean changes in outcome measures from baseline (pre) to end point (post) for each intervention group (that is, DI or DC), data were entered in RevMan with their corresponding number of participants and s's. For trials 40,41,43,44,46 that reported both pre-and post-intervention values, changes were computed by subtracting the pre-from the post-measurements. In case of missing s's, the s's were estimated by imputing s's of other studies using the same outcome measures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Where studies 38,39,51,55,56 reported mean changes in outcome measures from baseline (pre) to end point (post) for each intervention group (that is, DI or DC), data were entered in RevMan with their corresponding number of participants and s's. For trials 40,41,43,44,46 that reported both pre-and post-intervention values, changes were computed by subtracting the pre-from the post-measurements. In case of missing s's, the s's were estimated by imputing s's of other studies using the same outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…Given that intervention components vary considerably across studies, it is not possible to do so definitively; however, several salient considerations emerge from this review. An assessment limited to the findings of formal meta-analysis suggests that the following commonly used program components may be valuable: parent involvement (as discussed above), [37][38][39][40][41]43,44 classroom (or after-school) instruction on improving dietary intake or increasing PA, [37][38][39][40][41]43,44,46,49 participatory/hands-on, skill building student activities, [37][38][39][40][41]43,44,49 the provision of print materials, [37][38][39][40] teacher training for program implementation, 37-39 student competitions, 44 improvements to the nutritional environment (school cafeteria offerings, etc. ), 43,46 implementation of PA programs in addition to routine PE, 40,41,43 modifications to duration, frequency or intensity of existing PE, 46,49 use of non-competitive PA, 49 training in behavioral techniques (including self monitoring, goal setting, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Effects on adiposity were seen only in the Planet Health program, 2 and then only among girls. Reviewing an additional eight trials, Wareham et al 3 also found heterogeneous results: two trials achieved effects for boys but not girls, 4,5 while the others, including the elaborate Pathways program that ran for 3 years, 6 were unsuccessful in modifying adiposity. The US Task Force on Community Preventive Services concluded that the evidence on school-based interventions was not adequate to recommend them for obesity prevention.…”
Section: Introductionmentioning
confidence: 99%